AB0987 A longitudinal study of work disability among people with chronic knee pain. (23rd January 2014) - Agaliotis, M.; Bridgett, L.; Nairn, L.; Votrubec, M.; Jan, S.; Heard, R.; Fransen, M.
Abstract : Background: With an ageing population and increased trend to delay retirement worldwide, the number of people in the workforce affected by knee osteoarthritis will increase(1). There is a paucity of research examining the burden of work disability among people with knee osteoarthritis(2). Previous population and patient-based surveys have mostly been limited to evaluating absenteeism and have all required lengthy recall periods(2). Objectives: To determine the burden and risk factors associated with work disability (absenteeism and presenteeism) among people with chronic knee pain. Methods: A longitudinal study nested within a randomised controlled trial evaluating the long-term effect of dietary supplements. The study cohort consisted of the 336 (55%) trial participants in paid employment. A Participant Diary required reporting on days off work (absenteeism) and reduced productivity while at work (presenteeism) for seven days, every two months over a 12 month follow up period. Baseline risk factors included knee pain, patient global assessment, occupational group, radiographic disease severity, physical activity, body mass index, health-related quality of life (SF-12) and self-reported co-morbidity. Results: Among the 336 participants in paid employment, 36 (12%) withdrew from the LEGS study during the 12 month follow up period. A total of 219 (65%) completed all six Participant Diaries while 269 (80%) completed at least five of the six Participant Diaries. Most participants were in professional and managerial roles (46%) and less than 60 years of age (69%). While all participants had medial tibiofemoral joint space narrowing in at least one knee, most knees were Kellgren and Lawrence grade 1 or 2 (∼90%) indicating mild to moderate radiographic disease(3). Over the 12 month follow up period, 44 (13%) participants reported 1 or more days off work due to knee problems. Almost half (43%) of the cohort reported <90% work productivity due to their knee problems over the 12 month follow up period. In multivariate analysis, the only significant risk factor for absenteeism was SF-12 PCS <40 (OR: 3.70 [95% CI: 1.34-10.18]). Significant risk factors for presenteeism included; aged 55 - 64 years (OR: 1.92 [1.02-3.61]), SF-12 PCS <49 (OR: 1.94 [95% CI: 1.01-3.73), manual work (OR: 7.63 [1.67-34.79]) and maximum knee pain rated as 4 – 6 (out of 10) (OR: 2.11 [1.08-4.16]). Conclusions: This longitudinal study demonstrated marked work disability among people with chronic knee pain, but mostly only mild radiographic disease severity. Physical disability, older age, manual labour and knee pain were clearly associated with reduced productivity while at work. References: Woolf AD, Pfleger B. Burden of major musculoskeletal conditions. [Review] [69 refs]. Bull World Health Organ 2003;81:646-56. Bieleman HJ, Oosterveld FG, Oostveen JC, Reneman MF, Groothoff JW. Work participation and health status in early osteoarthritis of the hip and/or knee: a comparison between the Cohort Hip and Cohort Knee and the Osteoarthritis Initiative. Arthritis Care Res 2010;62:683-9. Kellgren JH, Lawrence JS. Radiological assessment of osteo-arthrosis. Ann Rheum Dis 1957;16:494-502. Disclosure of Interest: None Declared